The effect of land fragmentation on farmers’ rotation behavior in rural China - Yang, Boqiong; Duan, Yuxin; Zhao, Qiran (Frontiers in Environmental Science, 2022)
[Background] Arable land protection is the key to guaranteeing food security in China, as well as protecting the ecological environment and ensuring the continuous increase of farmers’ income. Crop rotation is one of the many forms of arable land protection. [Objectives] In this paper, we aim to estimate the possible influence of land fragmentation, famers’ willingness to rotate, and farmers’ rotation behavior in China. Combining farmers’ willingness to rotate and farmers’ rotation behavior using the theory of intermediary effect, we determine whether the degree of land fragmentation will affect farmers’ willingness to rotate or not, thereby affecting farmers’ rotation behavior. [Methodology] This study based on the field survey conducted in Heilongjiang Province in 2018, focused on the impact of land fragmentation on farmers’ rotation behavior through OLS and Probit model. Specifically, the degree of land fragmentation and farmers’ willingness to rotate are 0.187 and 0.463, respectively. Further, by taking the farmers’ willingness to rotate as the mediator, this paper discusses the mechanism on the effect of land fragmentation on farmers’ rotation behavior. Finally, the farmers are divided into large and small farmers—according to acreage for heterogeneity analysis. [Main findings] This study found that the degree of land fragmentation affects farmers’ willingness to rotate, thereby having some mediating effects on farmers' rotation behavior. [Conclusion] The indirect impact accounts for only 39.86% of the total impact, and more comes from the direct impact. Thus, policy makers should strengthen the guidance for farmers to stimulate their behavior and willingness to implement rotation. Furthermore, it is vital to improve the popularization of arable land protection knowledge and increase crop rotation subsidies.